Kelayakan Agribisnis dan Evaluasi Organoleptik Olahan Daging Ayam dengan Penambahan Kelakai Merah sebagai Diversifikasi Pangan Fungsional - Riskayanti Riskayanti; Firdaus Husein; Monasdir Monasdir (Program Studi Agribisnis Fakultas Pertanian, 2026)
This study aimed to analyze the organoleptic quality and agribusiness feasibility of chicken meat products—sausages, nuggets, and meatballs—with the addition of red kelakai (Stenochlaena palustris) as a functional food diversification ingredient. The research employed organoleptic testing on color, aroma, taste, texture, and overall acceptability using 25 semi-trained panelists, along with an agribusiness feasibility analysis based on the revenue-to-cost ratio (R/C) at a small-scale production capacity (10 kg/day). The results showed that both the form and level of red kelakai addition significantly affected (P<0.01) all organoleptic parameters except texture. Fresh kelakai yielded higher sensory scores than powdered kelakai, with the best overall acceptance at the 5% addition level. Additions above 10% decreased panelists’ acceptance due to darker color and stronger herbal flavor. From an economic perspective, all products had an R/C ratio greater than 1, indicating economic feasibility. The highest value was found in chicken nuggets (R/C = 1.49), followed by meatballs (1.45) and sausages (1.43). In conclusion, adding up to 5% red kelakai in chicken-based products is optimal in terms of sensory quality and economic value. This innovation demonstrates the potential for developing functional food products based on local ingredients, offering added value for agribusiness development and small-scale food enterprises.